KONSTRUKSI INSTRUMEN PENILAIAN AUTENTIK (AUTHENTIC ASSESSMENT) DALAM MENGEVALUASI PRAKTIK IBADAH SISWA DI SMP NEGERI 1 MALO (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the phenomenon of Islamic Religious Education (PAI) learning evaluation, which tends to be dominated by written cognitive tests, thus failing to capture students' actual competencies in the psychomotor and affective aspects, particularly in worship practices. The objectives of this study were: (1) Analyze the need for authentic assessment instruments at SMP Negeri 1 Malo; (2) Construct valid and reliable authentic assessment instruments to evaluate worship practices; and (3) Test the effectiveness of these instruments in improving the accuracy of teacher assessments. The research method used was Research and Development (R&D) with a simplified Borg & Gall development model, encompassing preliminary study, planning, product draft development, expert validation (materials and evaluation), field trials, and final product revision. The subjects of this study were seventh/eighth grade students at SMP Negeri 1 Malo and the PAI subject teachers who used the instruments. Data were collected through interviews, observations, and questionnaires, and analyzed descriptively using qualitative and quantitative methods. The research results indicate that the developed authentic assessment instrument, consisting of a performance observation sheet, self-assessment, and peer- assessment, was constructed using a measurable assessment rubric. Expert validation results indicated that the instrument was categorized as